2021
DOI: 10.3389/fpsyg.2021.681940
|View full text |Cite
|
Sign up to set email alerts
|

Differential Associations Between Parents' Versus Children's Perceptions of Parental Socialization Goals and Chinese Adolescent Depressive Symptoms

Abstract: Although prior studies have demonstrated the associations between parental socialization goals and parenting practices, as well as parenting practices and adolescent depressive symptoms, respectively, research examining the comprehensive developmental pathways among these constructs (i. e., the path from parental socialization goals to parenting practices to adolescent depressive symptoms) is scarce, especially in the Chinese context. Grounded in the integrative model of parenting, this study investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…This affords a more complete picture of the mindful parenting process in families, accounting for the subjectivity of experience (Boyce et al, 1998;Schaefer, 1965). Children's subjective experiences of parenting are robust predictors of child outcomes (Danese & Widom, 2020;Zhou et al, 2021), and identifying determinants of child-reported mindful parenting may improve our understanding. Second, a multi-informant approach may also increase the validity of the mindful parenting process model by minimising bias in self-report of parenting (Morsbach & Prinz, 2006;Schofield et al, 2016) and common-method variance where determinants are also parent-reported (Burk & Laursen, 2010).…”
Section: Mindful Parentingmentioning
confidence: 99%
“…This affords a more complete picture of the mindful parenting process in families, accounting for the subjectivity of experience (Boyce et al, 1998;Schaefer, 1965). Children's subjective experiences of parenting are robust predictors of child outcomes (Danese & Widom, 2020;Zhou et al, 2021), and identifying determinants of child-reported mindful parenting may improve our understanding. Second, a multi-informant approach may also increase the validity of the mindful parenting process model by minimising bias in self-report of parenting (Morsbach & Prinz, 2006;Schofield et al, 2016) and common-method variance where determinants are also parent-reported (Burk & Laursen, 2010).…”
Section: Mindful Parentingmentioning
confidence: 99%
“…Parental psychological control refers to parents’ attempts to interfere with their children’s mental and emotional development ( Zhou et al, 2021 ). In China, parental control has been determined to be negatively correlated with children’s mental health, which will destroy children’s sense of autonomy at the appropriate age, thus leading to the misbehavior of teenagers and damaging their mental health ( Zhou et al, 2017 ; Shek et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parental control includes behavioral control and psychological control ( Barber, 1996 ). Studies have proved that parental behavioral control can promote the good development of children and adolescents, while psychological control is not conducive to their physical and mental health, and may inhibit their emotions ( Barber et al, 2005 ; Wang et al, 2007 ; Sheldon, 2011 ; Zhou et al, 2021 ). However, one study demonstrated that parental control was positively associated with children’s mental health in China when used occasionally ( Shek and Lee, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parental psychological control refers to parents' attempts to interfere with their children's mental and emotional development (Zhou et al, 2021). In China, parental control has been determined to be negatively correlated with children's mental health, which will destroy children's sense of autonomy at the appropriate age, thus leading to the misbehavior of teenagers and damaging their mental health Shek et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Parental control includes behavioral control and psychological control (Barber, 1996). Studies have proved that parental behavioral control can promote the good development of children and adolescents, while psychological control is not conducive to their physical and mental health, and may inhibit their emotions (Barber et al, 2005;Sheldon, 2011;Zhou et al, 2021). However, one study demonstrated that parental control was positively associated with children's mental health in China when used occasionally (Shek and Lee, 2007).…”
Section: Introductionmentioning
confidence: 99%